2010
DOI: 10.1063/1.3431396
|View full text |Cite|
|
Sign up to set email alerts
|

Study of defect-induced ferromagnetism in hydrogenated anatase TiO2:Co

Abstract: Electronic and magnetic properties of Co-doped TiO2 polycrystalline pellets (Ti0.95Co0.05O2) have been investigated using x-ray diffraction, x-ray photoemission, magnetization, and resistance measurements. The as-synthesized and hydrogenated specimens crystallize in the anatase type tetragonal structure containing very small (∼4.4%) rutile phase. The dopant ions of Co are found to be divalent and well incorporated into TiO2 lattice, substituting the Ti site within the anatase phase, with no evidence of metalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 31 publications
4
19
1
Order By: Relevance
“…Doping of Cu increases the concentration of grain boundary defects. This observation is supported by a report of Singhal et al (2010) who examined that oxygen vacancies generated on doping migrate to the grain boundary and thereby increases defect content in this region. Similarly, Gu et al (2009) ions.…”
Section: Cu Doping Effect On Shallow and Deep Level Emission And Quensupporting
confidence: 71%
“…Doping of Cu increases the concentration of grain boundary defects. This observation is supported by a report of Singhal et al (2010) who examined that oxygen vacancies generated on doping migrate to the grain boundary and thereby increases defect content in this region. Similarly, Gu et al (2009) ions.…”
Section: Cu Doping Effect On Shallow and Deep Level Emission And Quensupporting
confidence: 71%
“…Meanwhile, the observed induction and weaken of the ferromagnetism shows close relationship with the valence charged oxygen vacancies (Cu 1+ -V O ). Our results present a quantitative relationship between the defect complexes of Cu 1+ -V O and the induced RTFM in milled CuO, similar to the reports on TiO 2 and CeO 2 , 23,24 where the Ti ions in TiO 2 (Ce ions in CeO 2 ) transforming from 4+ to 3+ state, accompanied by creation of V O , were related to the RTFM. Recently, Singhal et al also reported the RTFM in pristine anatase TiO 2 paramagnetic bulk through extended hydrogenation.…”
supporting
confidence: 75%
“…Among potential DMSs materials such as TiO 2 , ZnO, SnO 2 and In 2 O 3 , TM-doped TiO 2 has been extensively studied and regardless as one of the most likely candidates due to its high surface area and high availability of defect sites for trapping electrons, making them an ideal candidate for the origin of room temperature ferromagnetism (RTFM). [6][7][8][9][10][11][12][13] However, a number of studies indicates that the RTFM in TM-doped TiO 2 might occur due to precipitation of magnetic clusters or from secondary magnetic phases. 6,7 On the other hand, some recent reports rule out the strong connection between dopant clustering and the reported ferromagnetism and also suggest intrinsic ferromagnetism due to the presence of oxygen vacancies defects.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 On the other hand, some recent reports rule out the strong connection between dopant clustering and the reported ferromagnetism and also suggest intrinsic ferromagnetism due to the presence of oxygen vacancies defects. [8][9][10][11][12][13] Obviously, the origin of ferromagnetism in oxide DMSs remains a very controversial topic.…”
Section: Introductionmentioning
confidence: 99%